Fostering literary creativity through emotional experience: a systematic review of poetry writing instruction in elementary education - I Gede Dodik Sanjiartha; Ni Nyoman Lisna Handayani; Gusti Ngurah Arya Yudaparmita (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Poetry writing instruction in Indonesian elementary schools has often emphasized technical mastery while neglecting students' emotional engagement, resulting in formulaic compositions lacking authentic expression. This systematic literature review examined empirical evidence on how emotional experience-based approaches influence elementary students' literary creativity in poetry writing, with a focus on Indonesian contexts while drawing on international evidence. Following PRISMA 2020 guidelines, 38 empirical studies (qualitative, quantitative, and mixed-methods) published between 2018 and 2025 were synthesized from Scopus, ERIC, Google Scholar, Garuda, and SINTA databases. Analysis revealed three key mechanisms through which emotional experience enhanced literary creativity: (1) emotional scaffolding that activated personal memories as creative resources, evidenced by significantly higher originality scores across multiple studies; (2) dialogic reflection processes that transformed raw emotions into poetic language through social mediation; and (3) safe expressive spaces that reduced writing anxiety and encouraged linguistic risk-taking, correlating with greater emotional depth in student poetry. Implementation challenges included teachers' limited training in affective pedagogy and assessment systems prioritizing technical correctness. The findings synthesize existing theoretical and empirical grounding for developing emotionally-responsive poetry writing modules and highlight the need for context-sensitive teacher professional development.